2005
DOI: 10.1007/s10800-005-9083-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the corrosion behavior of galvannealed steel in chloride aqueous solution and in tropical marine environment

Abstract: An investigation was made into the corrosion behavior of commercial galvannealed steel in 10 )2 mol dm )3 NaCl aqueous solutions and in a tropical marine environment, using scanning electron microscopy (SEM), galvanostatic electrochemical stripping (GES), potentiodynamic linear polarization (PLP), and electrochemical impedance spectroscopy (EIS) techniques and open circuit measurements (E oc ). For purposes of comparison, a commercial galvanized steel was also subjected to similar corrosion tests. GES and SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…These results show that the corrosion performance of these electrodeposits is superior to that of plain Zn coatings. [1][2][3][4][5][6][7][8][9][10][11][12] An important aspect, from a practical and technological standpoint, is that these coatings must still have a high Zn content to maintain the cathodic protection of the steel substrate while still remaining less active than just Zn coatings. Additionally, due to environmental and health considerations, these zinc alloy coatings have been proposed as potential candidates to replace highly carcinogenic Cd coatings in anticorrosive applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that the corrosion performance of these electrodeposits is superior to that of plain Zn coatings. [1][2][3][4][5][6][7][8][9][10][11][12] An important aspect, from a practical and technological standpoint, is that these coatings must still have a high Zn content to maintain the cathodic protection of the steel substrate while still remaining less active than just Zn coatings. Additionally, due to environmental and health considerations, these zinc alloy coatings have been proposed as potential candidates to replace highly carcinogenic Cd coatings in anticorrosive applications.…”
Section: Introductionmentioning
confidence: 99%
“…8 A previous study showed that the corrosion mechanism of Zn-Fe coatings presented a good correlation between a long-term total immersion laboratory test in NaCl solution and a natural exposing test in marine atmosphere for 3 years. 1 In the industrial plating process, the low Co content in the electrodeposited Zn-Co layer (≅ 1% / wt.%) is associated to the presence of commercial additives in the plating solutions, such as levelers or brighteners, because the use of additives makes it possible to obtain layers with a decorative appearance. Industrial additives contain complexing agents that form stable complexes with cobalt ions that hinder the cobalt deposition.…”
Section: Introductionmentioning
confidence: 99%
“…19 The GA layer before the electrochemical dissolution showed the presence of stick crystal, which is a characteristic of the zeta phase, and columnar crystal, which is typical of the delta phase. 18 According to XRD results, which were obtained in a previous work, the delta phase is predominant in galvanneal layer (62.3% of counts per second), followed by the gamma (27.6%) and zeta (10.1%) phases. 15 In the coulometric dissolution, each phase dissolves at a characteristic potential, which was in a range between 2860 and 2855 mV(SCE) for the zeta phase, 2808 and 2798 mV(SCE) for the delta phase and between 2721 and 2716 mV(SCE) for the gamma phase.…”
Section: Discussionmentioning
confidence: 79%
“…47,48 The latter is related to the diffusion of the zinc oxidation products to the bulk solution or to oxygen reduction. 11,[48][49][50] Associated with the decrease in impedance modulus in mid-and lowfrequency regions is a decrease and shift of the phase angle of the first time-constant toward lower frequencies and a decrease of the phase angle of the second time-constant. This can be related to the decreased corrosion resistance of the reference system.…”
Section: Resultsmentioning
confidence: 99%